Maintenance of Cross-Cut Saws - Singh, S. Niranjan (Indian Forester, 1959)
This paper deals briefly with the important subject of maintenance of cross-cut saws. Even the best tools do not give efficient service if these are not properly maintained. An effort has been made to describe easy and efficient methods of maintenance of the triangulartoothed saw, raker-toothed saw and bow-saw.